A new colorful species of Pristimantis (Anura: Craugastoridae) from the eastern flank of the Cordillera Central in Colombia - Rivera-Prieto, Diego A.; Rivera-Correa, Mauricio; Daza, Juan M. (Zootaxa, 2014)
We describe a new species of Pristimantis from the humid forests on the eastern flank of the northern Cordillera Central in Colombia (6º 23’ 19.3554" N, 75º 1’ 24.0594" W; ca. 1150 m.a.s.l.). Pristimantis jaguensis sp. nov. is characterized by an extraordinary variation in color and is readily distinguished from congeneric species by lacking nuptial pads, discoidal fold and conical calcar tubercles; flanks and belly white to cream without blotches as well as iris yellow ocher to copper with thick brown reticulation and cream sclera. Molecular phylogenetic analyses recovered the new species in a clade with species mostly distributed in Ecuador. Our finding suggests that new taxa can still be discovered in the Middle Magdalena River valley of Colombia despite the extensive sampling this region has received during the last decades.